2022
DOI: 10.3390/healthcare10112127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Smoking Behavior of Older Adults’ Oral Health

Abstract: While smoking is a crucial health risk, it adversely affects oral health, particularly becoming riskier for older adults who have smoked for a long time. This study identifies the patterns of smoking behavior changes in older adults aged 65 years and older and examines how the smoking behavior changes affect their oral health. Longitudinal data were derived from Korean Longitudinal Study of Aging (KLoSA) between 2006 and 2018, targeting the older adults 65 years and older in South Korea. The independent variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…According to Margolis's research, it was indicated that well-educated, re-tired older adults may practice healthier behaviors, especially when they face new chronic diseases and start to make healthy behavior changes [78]; many studies have also confirmed that the level of education is related to practicing healthy behaviors [79][80][81][82]. The smoking habits of males and females were significantly different, which was consistent with many prior studies [73,[83][84][85]; moreover, the majority of older smokers were male [86]. In this study, among the older adults who were non-smokers and ex-smokers, 72% were male and 96% were female.…”
Section: Discussionsupporting
confidence: 65%
“…According to Margolis's research, it was indicated that well-educated, re-tired older adults may practice healthier behaviors, especially when they face new chronic diseases and start to make healthy behavior changes [78]; many studies have also confirmed that the level of education is related to practicing healthy behaviors [79][80][81][82]. The smoking habits of males and females were significantly different, which was consistent with many prior studies [73,[83][84][85]; moreover, the majority of older smokers were male [86]. In this study, among the older adults who were non-smokers and ex-smokers, 72% were male and 96% were female.…”
Section: Discussionsupporting
confidence: 65%